Functional and neurochemical disruptions of brain hub topology in chronic pain. Issue 4 (April 2019) - Kaplan, Chelsea M.; Schrepf, Andrew; Vatansever, Deniz; Larkin, Tony E.; Mawla, Ishtiaq; Ichesco, Eric; Kochlefl, Laura; Harte, Steven E.; Clauw, Daniel J.; Mashour, George A.; Harris, Richard E.
Abstract : Abstract: A critical component of brain network architecture is a robust hub structure, wherein hub regions facilitate efficient information integration by occupying highly connected and functionally central roles in the network. Across a wide range of neurological disorders, hub brain regions seem to be disrupted, and the character of this disruption can yield insights into the pathophysiology of these disorders. We applied a brain network–based approach to examine hub topology in fibromyalgia, a chronic pain condition with prominent central nervous system involvement. Resting state functional magnetic resonance imaging data from 40 fibromyalgia patients and 46 healthy volunteers, and a small validation cohort of 11 fibromyalgia patients, were analyzed using graph theoretical techniques to model connections between 264 brain regions. In fibromyalgia, the anterior insulae functioned as hubs and were members of the rich club, a highly interconnected nexus of hubs. In fibromyalgia, rich-club membership varied with the intensity of clinical pain: the posterior insula, primary somatosensory, and motor cortices belonged to the rich club only in patients with the highest pain intensity. Furthermore, the eigenvector centrality (a measure of how connected a region is to other highly connected regions) of the posterior insula positively correlated with clinical pain and mediated the relationship between glutamate + glutamine (assessed by proton magnetic resonance spectroscopy) within this structure and the patient's clinical pain report. Together, these findings reveal altered hub topology in fibromyalgia and demonstrate, for the first time to our knowledge, a neurochemical basis for altered hub strength and its relationship to the perception of pain. Abstract : Supplemental Digital Content is Available in the Text.Hub topology is altered in fibromyalgia, and disruption of the excitatory tone within the insula influences hub status and is associated with clinical pain intensity.